Doctrinal Analysis of Effects on Second Marriage Conducted by The Fake Documents (Case Study Court Decision No 67 / Pid.B / 2018 / PN.Kds) - Bayu Enggar Pramono; Akhmad Khisni (Jurnal Daulat Hukum, 2018)
The goal which achieved in this research is to know the legal consequences against criminal acts, what factors that affect crime, legal considerations the judge in meting out criminal sanctions against the perpetrators of criminal acts do a second marriage that is done on the basis of false documents (Case Study Court Decision No. 67/Pid. B/2018/PN. Kds).This research is the legal research which using Empirical Juridical approach or also called as the Juridical Sociological. According to this study, the level specified as descriptive research analytical. Data collection can be done using primary and secondary sources. Methods of data analysis used in this study is a qualitative analysis.The results of this research that is due to laws against the crime of second marriage dropping the criminal to the defendant therefore with imprisonment for 6 (six) months of the factors that influence crime who do the second marriage with the fake document. First, not given the permission of the first wife. Second, a conflict in the family. Third, still the presence of the community who do marry. Legal consideration of judges in meting out criminal sanctions against the perpetrators of the crime do the second marriage was appropriate i.e. with satisfy all the elements of the claim i.e. claims sole Article 279 paragraph 1 to 1 of the KUHP.Keyword: A Criminal Offence; The Marriage; The Judge's Consideration